A carbon monoxide catalyst and its preparation method

During the preparation of the carbon monoxide catalyst, the catalyst with porous structure is formed by mixing tetrabutyl titanate with alcohol reagent and platinum nitrate aqueous solution, which solves the problems of poor stability of the existing catalyst and single applicable environment, and realizes the catalyst High stability and complex environment applicability.

CN119076015BActive Publication Date: 2025-02-14HUNAN LITAI ENVIRONMENTAL ENG CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411569921.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing carbon monoxide catalysts have problems with poor stability and single applicable environment, including poor acid resistance, poor temperature tolerance, small specific surface area and few pore structures.

Method used

The tetrabutyl titanate is mixed with alcohol reagent to form a solution a, and the additive is added to the aqueous platinum nitrate solution to form a solution b. The two are mixed in an appropriate proportion to form a gel-like substance. After drying and calcining, the A catalyst of the porous structure is dispersed in water and added with a binder to form a slurry, coated onto the porous support for further drying and calcining.

Benefits of technology

The prepared catalyst has good stability and can be suitable for complex environments, and can effectively catalyze carbon monoxide in the sintered flue gas of steel, while releasing heat, meeting the requirements of the SCR denitrification process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119076015B_ABST
    Figure CN119076015B_ABST
Patent Text Reader

Abstract

This invention relates to the field of carbon monoxide catalyst technology, specifically to a carbon monoxide catalyst and its preparation method. The carbon monoxide catalyst is prepared by this method. The preparation method includes steps S1: mixing tetrabutyl titanate with an alcohol reagent to obtain solution a; adding an auxiliary agent to a platinum nitrate aqueous solution and mixing to obtain solution b; step S2: adding solution b dropwise to solution a and continuously stirring until a gel-like substance is formed; step S3: subjecting the gel-like substance to a first drying treatment and a first calcination treatment sequentially to obtain a powdered catalyst; step S4: grinding the powdered catalyst to a D90 < 5 μm and dispersing it in water, adding a binder to form a slurry; step S5: coating the slurry onto a porous support, and subjecting it to a second drying treatment and a second calcination treatment sequentially to obtain the carbon monoxide catalyst. The carbon monoxide catalyst prepared by this invention has good stability and can be used in complex environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon monoxide catalysts, and in particular to a carbon monoxide catalyst and a preparation method thereof. Background Art

[0002] Carbon monoxide is one of the important atmospheric pollutants, which poses a serious threat to the ecological environment and human health. Industrial flue gas is an important source of carbon monoxide emissions. Among them, the sintering flue gas emissions in the iron and steel smelting industry are large (the flue gas flow rate is 500,000 to 2 million Nm3 / h), the pollutant composition is complex (containing sulfur dioxide, nitrogen oxides, carbon monoxide and volatile organic gases and other pollutants), and the pollutant content is high, which seriously affects the air quality in the area where the steel mill is located. However, the emission reduction methods of sintering flue gas pollutants in the iron and steel smelting industry mainly adopt desulfurization and denitrification, and basically do not involve carbon monoxide emission reduction.

[0003] In denitrification and emission reduction, the selective catalytic reduction (abbreviated as SCR) technology has stable operation and high denitrification efficiency, and is favored by many companies. It is worth noting that the current operating temperature of the SCR catalyst is 180~280℃, which is 80~160℃ higher than the temperature of the sintering flue gas. Therefore, it is necessary to heat the flue gas before denitrification. The carbon monoxide in the sintering flue gas is a potential heat source. If the carbon monoxide can be completely oxidized into carbon dioxide, the heat released by the reaction can increase the flue gas temperature by 30~50℃, thereby saving a lot of energy consumption for the subsequent denitrification process.

[0004] Existing carbon monoxide catalysts have the problems of poor catalyst stability and a single applicable environment. For example, in the study on the carbon monoxide oxidation performance of sintering flue gas based on Pt-Ce-Ti catalyst published in the Journal of Central South University in 2022, Li Haoming et al. pointed out that the Pt-Ce-Ti powdered catalyst was prepared by impregnation method, and the carbon monoxide conversion rate could reach more than 99% when the reaction temperature was 120~160°C. However, under the condition of moisture and SO2 in the reaction atmosphere, the carbon monoxide conversion rate decreased and the catalyst activity decreased after 12 hours of operation. It can be seen that the Pt-Ce-Ti powdered catalyst has the problem of poor stability. Because the composition of sintering flue gas is very complex, it contains components such as sulfur, chlorine, water, dust, nitrogen oxides and heavy metals, which can easily have a great impact on the performance of the catalyst. The existing preparation of carbon monoxide catalysts is mostly limited to laboratory tests, and only considers the influence of single or individual factors on the performance of the catalyst, making the applicable environment single and difficult to reflect the real industrial application.

[0005] In addition, the common carriers used in the preparation of carbon monoxide catalysts include aluminum oxide carriers, silicon dioxide carriers and activated carbon carriers. Among them, aluminum oxide carriers have poor acid resistance and their structure is easily corroded and destroyed by steel sintering flue gas, resulting in the loss of loaded active components and additives; silicon dioxide carriers have problems of small specific surface area and few pore structures; activated carbon carriers have problems of poor temperature tolerance.

[0006] In summary, it is necessary to develop a carbon monoxide catalyst and a preparation method thereof, which can solve the problems of poor catalyst stability and single applicable environment of existing carbon monoxide catalysts on the one hand, and solve the problems of poor acid resistance, poor temperature tolerance, small specific surface area and few pore structures of the carrier on the other hand. Summary of the invention

[0007] The present invention aims to provide a carbon monoxide catalyst and a preparation method thereof. The specific technical scheme is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a carbon monoxide catalyst, comprising:

[0009] Step S1, tetrabutyl titanate and an alcohol reagent are mixed at a mass ratio of 1:1-4 to obtain a solution a; an auxiliary agent is added to a platinum nitrate aqueous solution and mixed to obtain a solution b; wherein the auxiliary agent includes at least one of a copper salt, a manganese salt and a cobalt salt; in the solution b, the total molar amount of copper, manganese and cobalt is 0.2-5 times that of platinum;

[0010] Step S2, at 40-70° C., adding the solution b dropwise to the solution a, and continuously stirring until a gel-like substance is formed; wherein the mass ratio of the solution a to the solution b is 1:0.1-0.5;

[0011] Step S3, subjecting the gel-like substance to a first drying treatment and a first calcination treatment in sequence to obtain a powdered catalyst;

[0012] Step S4, grinding the powdered catalyst to D90 < 5 μm, dispersing the powdered catalyst in water, adding a binder, and preparing a slurry;

[0013] Step S5, coating the slurry on a porous carrier, and sequentially performing a second drying treatment and a second calcination treatment to obtain a carbon monoxide catalyst.

[0014] Optionally, in step S1, the alcohol reagent includes any one of ethanol, 1-propanol and 1-butanol; and the mass fraction of the platinum nitrate aqueous solution is 0.5% to 2%.

[0015] Optionally, in step S2, the copper salt includes at least one of copper nitrate and copper sulfate; the manganese salt includes at least one of manganese nitrate and manganese sulfate; and the cobalt salt includes at least one of cobalt nitrate and cobalt sulfate.

[0016] Optionally, in step S3, the drying temperature used in the first drying treatment is 110-150° C., and the drying time is 4-12 hours; the baking temperature used in the first roasting treatment is 500-700° C., and the roasting time is 4-6 hours.

[0017] Optionally, in step S4, the binder includes polyethylene glycol; the amount of the binder added is 5-15% of the mass of the powdered catalyst.

[0018] Optionally, in step S4, the solid content of the slurry is 20% to 30%.

[0019] Optionally, in step S5, the wet loading amount of the slurry coated on the porous carrier is 80-240 g / L.

[0020] Optionally, in step S5, the porous carrier is a cordierite honeycomb ceramic carrier.

[0021] Optionally, in step S5, the drying temperature used in the second drying treatment is 110-150° C., and the drying time is 4-12 hours; the baking temperature used in the second roasting treatment is 500-700° C., and the roasting time is 1-4 hours.

[0022] In a second aspect, the present invention provides a carbon monoxide catalyst prepared by the method for preparing the carbon monoxide catalyst.

[0023] The application of the technical solution of the present invention has at least the following beneficial effects:

[0024] The carbon monoxide catalyst of the present invention and its preparation method, the carbon monoxide catalyst prepared by the preparation method has good stability and can be applied to complex environments, such as being able to complete the catalytic degradation of carbon monoxide in steel sintering flue gas. In addition, carbon monoxide releases heat while being catalytically oxidized, so that the flue gas is heated up, meeting the requirements of the SCR denitrification process. The specific principle in the preparation process of the carbon monoxide catalyst is as follows: In step S1 of the preparation method, the a solution uses an alcohol reagent with an appropriate proportion to dilute tetrabutyl titanate, reduce the hydrolysis rate of tetrabutyl titanate, and gradually hydrolyze to generate TiO(OH)2; the b solution prepared by mixing platinum nitrate aqueous solution and an auxiliary agent is an acidic solution; in step S2, the acidic b solution is added dropwise to the a solution at an appropriate mass ratio, which can further reduce the hydrolysis rate of tetrabutyl titanate and facilitate the formation of a porous TiO2 gel-like substance. The specific hydrolysis reaction process is as follows:

[0025] Ti(OC4H9)4+ 3H2O=TiO(OH)2+4C4H9OH;

[0026] TiO(OH)2+H2O=Ti(OH)4;

[0027] Ti(OH)4+Ti(OC4H9)4=2TiO2+4C4H9OH;

[0028] Ti(OH)4+Ti(OH)4=2TiO2+4H2O;

[0029] During the hydrolysis process, Pt, Cu, Co, and Mn exist in the hydrolysis system in the form of ions. Under continuous stirring at 40-70°C, the solvent on the surface of the gel-like substance evaporates continuously, while the solvent in its pores cannot be evaporated in time. Pt, Cu, Mn, and Co in the form of ions slowly diffuse into the solvent in the pores, and then gradually and evenly adhere to the inner wall of the pores. Compared with ordinary impregnation, the present invention adopts step S2 to not only make the active component Pt and the auxiliary agents Cu, Mn, and Co exist on the surface of the gel-like substance, but also can be deeply combined on the inner wall of its pores, showing better dispersibility and stronger binding stability, and improving the stability of the catalyst. The obtained gel-like substance is treated by steps S3-S5 to obtain a carbon monoxide catalyst, wherein in step S4, the powdered catalyst is ground to D90 <5μm to avoid the particle size being too large and sinking to the bottom of the slurry and thus failing to form a uniformly dispersed slurry. Among them, in the process of forming a carbon monoxide catalyst, the additives Cu, Mn and Co can be oxidized into corresponding oxides, which can provide lattice oxygen when catalyzing carbon monoxide, thereby improving the catalytic efficiency of carbon monoxide; when catalyzing carbon monoxide, the active component Pt adsorbs and activates oxygen molecules to produce active oxygen, which can reduce the activation energy required for the carbon monoxide reaction and improve the catalytic efficiency of carbon monoxide. In the b solution, the total molar amount of copper, manganese and cobalt is controlled to be 0.5 to 5 times that of platinum, which, on the one hand, facilitates providing sufficient lattice oxygen for the catalytic oxidation reaction and improves the conversion rate of the catalyst; on the other hand, it avoids excessive coverage of the active sites of Pt by the additives, thereby reducing the conversion rate. In addition, the present invention adopts TiO2 gel-like substance as a porous carrier for attaching active component Pt and additives Cu, Mn and Co. This is because TiO2 gel-like substance has acid resistance compared with conventional alumina carriers, and its structure is not easily corroded and destroyed by steel sintering flue gas, thus avoiding the loss of active components and additives; TiO2 gel-like substance has a higher specific surface area and rich pore structure than conventional silica carriers; TiO2 gel-like substance has a higher temperature tolerance than conventional activated carbon carriers.

[0030] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 These are the test results of the stability and conversion rate of the carbon monoxide catalysts prepared in Examples 1-3 of the present invention;

[0033] Figure 2 These are the test results of the stability and conversion rate of the carbon monoxide catalyst prepared in Examples 4-5 of the present invention;

[0034] Figure 3 These are the test results of the stability and conversion rate of the carbon monoxide catalysts prepared in Examples 6-9 of the present invention;

[0035] Figure 4 These are the test results of the stability and conversion rate of the carbon monoxide catalyst prepared in Examples 10-11 of the present invention;

[0036] Figure 5 The stability and conversion rate test results of the carbon monoxide catalyst prepared in Comparative Example 1-2;

[0037] Figure 6 The stability and conversion rate test results of the carbon monoxide catalyst prepared in Comparative Example 3-4;

[0038] Figure 7 The stability and conversion test results of the carbon monoxide catalyst prepared in Comparative Examples 5-6;

[0039] Figure 8 is the nitrogen adsorption-desorption isotherm of the carbon monoxide catalyst prepared in Example 1 of the present invention;

[0040] Fig. 9 This is the pore size distribution diagram of the carbon monoxide catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0042] Embodiment 1:

[0043] A method for preparing a carbon monoxide catalyst comprises:

[0044] Step S1, tetrabutyl titanate and an alcohol reagent (specifically ethanol) are mixed at a mass ratio of 1:2 to obtain solution a; an auxiliary agent is added to a platinum nitrate aqueous solution and mixed to obtain solution b; wherein the auxiliary agent is copper nitrate; in the solution b, the molar amount of copper is 1 times that of platinum; the mass fraction of the platinum nitrate aqueous solution is 1%;

[0045] Step S2, at 50° C., adding the solution b dropwise to the solution a, and continuously stirring until a gel-like substance is formed; wherein the mass ratio of the solution a to the solution b is 1:0.3;

[0046] Step S3, subjecting the gel-like substance to a first drying treatment and a first calcination treatment in sequence to obtain a powdered catalyst; the first drying treatment adopts a drying temperature of 120° C. and a drying time of 6 hours; the first calcination treatment adopts a calcination temperature of 600° C. and a calcination time of 5 hours;

[0047] Step S4, grinding the powdered catalyst to D90 < 5 μm and then dispersing in water, adding a binder (specifically polyethylene glycol) to prepare a slurry; the amount of the binder added is 10% of the mass of the powdered catalyst; the solid content of the slurry is 25%;

[0048] Step S5, coating the slurry on a porous carrier (specifically a cordierite honeycomb ceramic carrier), and sequentially performing a second drying treatment and a second calcination treatment to obtain a carbon monoxide catalyst; the wet loading of the slurry coated on the porous carrier is 150 g / L; the drying temperature used in the second drying treatment is 120°C, and the drying time is 6 hours; the calcination temperature used in the second calcination treatment is 600°C, and the calcination time is 2 hours.

[0049] Embodiment 2:

[0050] Different from Example 1, in step S1, tetrabutyl titanate and ethanol are mixed at a mass ratio of 1:4 to obtain solution a.

[0051] Embodiment 3:

[0052] Different from Example 1, in step S1, tetrabutyl titanate and ethanol are mixed at a mass ratio of 1:1 to obtain solution a.

[0053] The carbon monoxide catalysts prepared in Examples 1-3 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 1 The test method is as follows:

[0054] The carbon monoxide catalyst was loaded into the reactor of the test device, wherein the loading size of the carbon monoxide catalyst was 100mm×100mm×100mm; the test device was connected to the steel sintering flue gas, and the gas collection position was after the desulfurization and denitrification of the steel sintering flue gas; the air intake flow rate was 15m³ / h; the air intake temperature was 280℃; a handheld carbon monoxide concentration analyzer was used to test the carbon monoxide concentration at the inlet and outlet of the test device.

[0055] Example 1-3 The ratio of tetrabutyl titanate to ethanol was changed. Figure 1 It is known that the stability of the carbon monoxide catalysts prepared in Examples 1-3 is basically the same, and they can all operate stably in a 20-day test. However, the conversion rate of the carbon monoxide catalyst prepared in Example 1 is relatively high, followed by Example 2, and Example 3 is relatively the worst. The reasons are analyzed as follows: In Example 2, the amount of ethanol used is relatively large, and the amount of tetrabutyl titanate used is relatively small, resulting in a slow hydrolysis rate of tetrabutyl titanate, an incomplete hydrolysis reaction, and a relatively small amount of gel-like substance formed, and relatively few active components and additives attached, and thus a relatively low conversion rate. In Example 3, the amount of ethanol used is relatively small, and the amount of tetrabutyl titanate used is relatively large, resulting in a relatively fast hydrolysis rate of tetrabutyl titanate, and finally the diffusion rate of the active component cannot catch up with the hydrolysis rate, so that the uniformity of the active component dispersion is not high, resulting in poor activity and reduced conversion rate.

[0056] Embodiment 4:

[0057] The difference from Example 1 is that in step S1, the molar amount of copper in the b solution is twice that of platinum.

[0058] Embodiment 5:

[0059] Different from Example 1, in step S1, the molar amount of copper in the b solution is 0.2 times that of platinum.

[0060] The carbon monoxide catalysts prepared in Examples 4-5 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 2 The test method is the same as that of Examples 1-3.

[0061] Example 4-5 changes the dosage of the auxiliary agent copper nitrate, from Figure 2 It is known that the stability of the carbon monoxide catalysts prepared in Examples 4-5 is basically the same, and they can all operate stably in a 20-day test. Compared with Example 1, the amount of copper used in Example 4 is relatively large, resulting in the covering of some of the active sites of Pt, and the carbon monoxide catalyst conversion rate is lower than that in Example 1. In Example 5, the amount of copper used is relatively small, and although it will not cover the active sites of Pt, it cannot provide sufficient lattice oxygen, resulting in a low carbon monoxide catalyst conversion rate.

[0062] Embodiment 6:

[0063] Different from Example 1, in step S1, the auxiliary agent further includes cobalt nitrate; and the molar ratio of copper, cobalt and platinum in the solution b is 1:1:1.

[0064] Embodiment 7:

[0065] Different from Example 1, in step S1, the auxiliary agents are manganese nitrate and cobalt nitrate; and the molar ratio of manganese, cobalt and platinum in the solution b is 1:1:1.

[0066] Embodiment 8:

[0067] Different from Example 1, in step S1, the auxiliary agents are copper nitrate, manganese nitrate and cobalt nitrate; and the molar ratio of copper, manganese, cobalt and platinum in the b solution is 1:1:1:1.

[0068] Embodiment 9:

[0069] Different from Example 1, in step S1, the auxiliary agents are copper sulfate, manganese sulfate and cobalt sulfate; and the molar ratio of copper, manganese, cobalt and platinum in the b solution is 1:1:1:1.

[0070] The carbon monoxide catalysts prepared in Examples 6-9 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 3 The test method is the same as that of Examples 1-3.

[0071] Example 6-9 changed the type of auxiliary agent, from Figure 3 It is known that the stability of the carbon monoxide catalysts prepared in Examples 6-9 is basically the same, and they can all operate stably in a 20-day test. Compared with Example 1, the use of multiple additives in Example 6-9 is beneficial to improving the conversion rate of the carbon monoxide catalyst. The reason is that when the additives are mixed with copper, manganese and cobalt, composite oxides (such as copper-manganese composite oxides, manganese-cobalt composite oxides and copper-manganese-cobalt composite oxides, etc.) are formed. There is migration and transfer of oxygen between the composite oxides. After the additives generate lattice oxygen, the migration and transfer ability of the lattice oxygen is enhanced under the support of the composite oxide, which improves the utilization efficiency of the lattice oxygen, making it easier to react with carbon monoxide, thereby improving the conversion rate.

[0072] Embodiment 10:

[0073] Different from Example 8, in step S2, the mass ratio of the a solution to the b solution is 1:0.5.

[0074] Embodiment 11:

[0075] Different from Example 8, in step S2, the mass ratio of the a solution to the b solution is 1:0.1.

[0076] The carbon monoxide catalysts prepared in Examples 10-11 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 4 The test method is the same as that of Examples 1-3.

[0077] Example 10-11 changes the ratio of solution a to solution b, Figure 4 It is known that the stability of the carbon monoxide catalysts prepared in Examples 10-11 is basically the same, and they can all operate stably in a 20-day test. Compared with Example 8, the carbon monoxide catalysts prepared in Examples 10-11 can achieve similar conversion rates.

[0078] Comparative Example 1:

[0079] Different from Example 1, in step S1, tetrabutyl titanate and ethanol are mixed at a mass ratio of 1:0.5 to obtain solution a.

[0080] Comparative Example 2:

[0081] Different from Example 1, in step S1, tetrabutyl titanate and ethanol are mixed at a mass ratio of 1:5 to obtain solution a.

[0082] The carbon monoxide catalysts prepared in Comparative Examples 1-2 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 5 The test method is the same as that of Examples 1-3.

[0083] Comparative Example 1-2 changed the ratio of tetrabutyl titanate to ethanol. Figure 5 It is known that compared with Example 1, the stability of the carbon monoxide catalyst prepared in Comparative Examples 1-2 is significantly reduced, and it can only operate stably in a 12-day test, and the initial conversion rate is also significantly reduced. Compared with Example 1, in Comparative Example 1, the amount of ethanol used is too little, and the amount of tetrabutyl titanate used is too much, resulting in a too fast hydrolysis rate of tetrabutyl titanate, making it difficult to form a structurally stable gel-like substance, and then it is difficult to form a structurally stable carbon monoxide catalyst, resulting in a significant decrease in stability and initial conversion rate. In Comparative Example 2, the amount of ethanol used is too much, and the amount of tetrabutyl titanate used is too little, resulting in insufficient hydrolysis of tetrabutyl titanate, making it difficult to form a structurally complete carbon monoxide catalyst, resulting in a significant decrease in stability and initial conversion rate.

[0084] Comparative Example 3:

[0085] Different from Example 1, no auxiliary agent is used in step S1.

[0086] Comparative Example 4:

[0087] The difference from Example 1 is that in step S1, the molar amount of copper in the b solution is 6 times that of platinum.

[0088] The carbon monoxide catalysts prepared in Comparative Examples 3-4 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 6 The test method is the same as that of Examples 1-3.

[0089] Comparative Example 3-4 changed the dosage of the auxiliary agent. Figure 6 It is known that compared with Example 1, the stability of the carbon monoxide catalyst prepared in Comparative Examples 3-4 is significantly reduced, and the initial conversion rate is also significantly reduced. Compared with Example 1, in Comparative Example 3, the carbon monoxide catalyst can only operate stably in a 12-day test, and the initial conversion rate is about 40%; wherein, the low conversion rate is because no auxiliary agent is used, and lattice oxygen cannot be provided, resulting in a low conversion rate; the poor stability should be due to the fact that no auxiliary agent is used. When poisonous substances are present, the poisonous substances cannot be combined with the auxiliary agent first, and can only be combined with the active component Pt, resulting in Pt poisoning and decreased catalyst stability. In Comparative Example 4, the carbon monoxide catalyst can only operate stably in a 15-day test, with an initial conversion rate of about 40%; wherein, the low conversion rate and poor stability are because the copper content of the auxiliary agent is too much, resulting in the active sites of Pt being covered, or the pores of the carrier being blocked, and carbon monoxide cannot be effectively adsorbed-catalyzed-desorbed, resulting in low conversion rate and poor stability.

[0090] Comparative Example 5:

[0091] Different from Example 8, in step S2, the mass ratio of the a solution to the b solution is 1:0.01.

[0092] Comparative Example 6:

[0093] Different from Example 1, in step S2, the mass ratio of the a solution to the b solution is 1:1.

[0094] The carbon monoxide catalysts prepared in Comparative Examples 5-6 were tested for carbon monoxide catalytic degradation stability and conversion rate. The test results are shown in Figure 7 The test method is the same as that of Examples 1-3.

[0095] Comparative Example 5-6 changed the ratio of solution a to solution b. Figure 7It is known that compared with Example 8, the amount of solution b added in Comparative Example 5 is small, the water content is small, the hydrolysis reaction basically cannot occur, and it is difficult to form a carbon monoxide catalyst with a complete structure, so the initial conversion rate is only 50%, and the conversion rate is close to 0 in the test on the 6th day. Compared with Example 1, the amount of solution b added in Comparative Example 6 is large, the water content is large, the hydrolysis reaction rate is too fast, and the diffusion rate of the active component cannot catch up with the hydrolysis rate, so that the active component is unevenly dispersed and cannot penetrate into the pores, resulting in a low initial conversion rate of the catalyst (about 45%) and poor stability. Among them, the conversion rate is close to 0 in the test on the 10th day.

[0096] In order to verify that the carbon monoxide catalyst prepared by the present invention is a mesoporous material, the present invention conducted nitrogen adsorption and desorption tests and pore size distribution analysis on the carbon monoxide catalyst prepared in Example 1. The test results are shown in Figure 8-Figure 9 The test method is as follows:

[0097] The characterization results of the specific surface area and pore volume of the carbon monoxide catalyst obtained in this test were obtained by the ASAP-2460 specific surface area and pore size analyzer produced by Mack, USA. The test mechanism of this analyzer is based on the BET adsorption theory. Before the test, the carbon monoxide catalyst sample needs to be crushed to less than 300 mesh, and then degassed at 150 ° C for 12 h to remove the guest molecules adsorbed in the pores of the material. The specific surface area data of the material is the N2 adsorption / desorption isotherm obtained at 77 K and 1 atm, and the characterization results are finally calculated by the BET equation.

[0098] Depend on Figure 8 It is known that the nitrogen adsorption-desorption isotherm of the carbon monoxide catalyst prepared in Example 1 of the present invention belongs to the IV isotherm, and the monolayer adsorption is saturated after point B, with a very obvious hysteresis loop, indicating that the catalyst is a typical mesoporous material. Among them, the hysteresis loop belongs to the H2 type, which is attributed to porous adsorbent or uniform particle accumulation.

[0099] Depend on Fig. 9 It is known that the pore size of the carbon monoxide catalyst prepared in Example 1 of the present invention is mostly between 2-16 nm. The specific surface area of ​​the catalyst is 20.033 m2 / g, and the average pore size is 6.565 nm.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon monoxide catalyst, characterized in that: include: Step S1, tetrabutyl titanate and an alcohol reagent are mixed at a mass ratio of 1:1-4 to obtain a solution a; an auxiliary agent is added to a platinum nitrate aqueous solution and mixed to obtain a solution b; wherein the auxiliary agent includes at least one of a copper salt, a manganese salt and a cobalt salt; in the solution b, the total molar amount of copper, manganese and cobalt is 0.2-5 times that of platinum; Step S2, at 40-70° C., adding the solution b dropwise to the solution a, and continuously stirring until a gel-like substance is formed; wherein the mass ratio of the solution a to the solution b is 1:0.1-0.5; Step S3, subjecting the gel-like substance to a first drying treatment and a first calcination treatment in sequence to obtain a powdered catalyst; Step S4, grinding the powdered catalyst to D90 < 5 μm, dispersing the powdered catalyst in water, adding a binder, and preparing a slurry; Step S5, coating the slurry on a porous carrier, and sequentially performing a second drying treatment and a second calcination treatment to obtain a carbon monoxide catalyst.

2. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In the step S1, the alcohol reagent includes any one of ethanol, 1-propanol and 1-butanol; and the mass fraction of the platinum nitrate aqueous solution is 0.5% to 2%.

3. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In step S2, the copper salt includes at least one of copper nitrate and copper sulfate; the manganese salt includes at least one of manganese nitrate and manganese sulfate; and the cobalt salt includes at least one of cobalt nitrate and cobalt sulfate.

4. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In the step S3, the drying temperature used in the first drying treatment is 110-150° C., and the drying time is 4-12 hours; the baking temperature used in the first calcination treatment is 500-700° C., and the baking time is 4-6 hours.

5. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In step S4, the binder includes polyethylene glycol; the amount of the binder added is 5% to 15% of the mass of the powdered catalyst.

6. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In step S4, the solid content of the slurry is 20% to 30%.

7. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In the step S5, the wet loading amount of the slurry coated on the porous carrier is 80-240 g / L.

8. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In the step S5, the porous carrier is a cordierite honeycomb ceramic carrier.

9. The method for preparing a carbon monoxide catalyst according to claim 1, characterized in that: In the step S5, the drying temperature used in the second drying treatment is 110-150° C., and the drying time is 4-12 hours; the baking temperature used in the second calcination treatment is 500-700° C., and the calcination time is 1-4 hours.

10. A carbon monoxide catalyst, characterized in that The catalyst is prepared by the method for preparing a carbon monoxide catalyst as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Hydrothermal-resistant and sulfur-tolerant overall structure combustion catalyst and preparation method thereof

    CN107983366A